2008
DOI: 10.1124/jpet.108.138941
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Isozymes Involved in Regulation of Secretion in Isolated Mouse Stomach in Vitro

Abstract: (Ϯ)-(E)-4-Ethyl-2-[(E)-hydroxyimino]-5-nitro-3-hexenamide](NOR-3), a nitric-oxide (NO) donor, is known to increase HCO 3 Ϫ secretion in rat stomachs, intracellularly mediated by cGMP; yet, there is no information about the phosphodiesterase (PDE) isozyme involved in this process. We examined the effects of various isozyme-selective PDE inhibitors on the secretion of HCO 3 Ϫ in the mouse stomach in vitro and the type(s) of PDE isozymes involved in the response to NO. The gastric mucosa of DDY mice was stripped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The muscle strips were incubated for 24 h with vehicle control (DMSO), and the specific antagonists to EP1 (SC-52342, Enzo, Plymouth Meeting, PA), EP1/EP2 (AH6809, Enzo), EP3 (L-798106, Tocris Bioscience, Ellisville, MO) and EP4 (ONO-AE 3-208, Haoyuan Chemexpress, Shanghai, China), separately. The concentration of 10 Ϫ5 M was chosen for all the antagonists because this was found effective in blocking respective EP receptor subtypes (4,18,32,48). Incubation with EP2 or EP4 antagonists did not significantly change colonic circular muscle contractility in sham control tissue (Fig.…”
Section: Involvement Of Ep Receptor Subtypes In the Regulation Of Colmentioning
confidence: 99%
“…The muscle strips were incubated for 24 h with vehicle control (DMSO), and the specific antagonists to EP1 (SC-52342, Enzo, Plymouth Meeting, PA), EP1/EP2 (AH6809, Enzo), EP3 (L-798106, Tocris Bioscience, Ellisville, MO) and EP4 (ONO-AE 3-208, Haoyuan Chemexpress, Shanghai, China), separately. The concentration of 10 Ϫ5 M was chosen for all the antagonists because this was found effective in blocking respective EP receptor subtypes (4,18,32,48). Incubation with EP2 or EP4 antagonists did not significantly change colonic circular muscle contractility in sham control tissue (Fig.…”
Section: Involvement Of Ep Receptor Subtypes In the Regulation Of Colmentioning
confidence: 99%
“…The gastric mucosal bicarbonate secretion is mediated by cGMP and Ca 2+ [60,61]. it has been shown that cGMP-induced bicarbonate secretion is mediated by COX/PGE 2 /EP1 receptor [62], so based on known signaling by this receptor, Ca 2+ is likely to be the most downstream messenger to elicit receptor actions. In contrast, evidence from cultured cells suggests that neither cAMP nor cGMP plays any role in gastric epithelial cell migration [21,63].…”
Section: Resultsmentioning
confidence: 99%